2018
DOI: 10.1002/ange.201807509
|View full text |Cite
|
Sign up to set email alerts
|

Recent Syntheses and Strategies toward Polycyclic Gelsemium Alkaloids

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…All of the expected products were observed in the finished reaction prior to exposure to water without any formation of silanol 15 N-46. After 180 h, the 15 N NMR peak with the greatest area appeared slightly downfield from the starting carbonazidate (Figure 5c). After exposing the reaction mixture to wet air, the peak disappeared, and a new peak that corresponded to silanol 15 N-46 appeared further upfield than the intermediate peak.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…All of the expected products were observed in the finished reaction prior to exposure to water without any formation of silanol 15 N-46. After 180 h, the 15 N NMR peak with the greatest area appeared slightly downfield from the starting carbonazidate (Figure 5c). After exposing the reaction mixture to wet air, the peak disappeared, and a new peak that corresponded to silanol 15 N-46 appeared further upfield than the intermediate peak.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…The results of our calculations predict that the former is overall energetically favored over the latter, but we describe below why neither can be ruled out completely simply based on the energiesin other words, both pathways are possible and could be simultaneously operative. To garner experimental support for the mechanism that was based on our calculations, an NMR study was performed using a 15 N-labeled carbonazidate 15 N-41 in CDCl 3 at 75 °C under extremely anhydrous conditions (Figure 5a). The 13 C NMR spectrum showed that intermediate α-diazo oxazolone 15 N-43 was formed after 40 h and then consumed after 180 h (Figure 5b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 3. Asymmetric Total Synthesis of (−)-14-Acetoxygelsedilam (3), (−)-14-Hydroxygelsenicine (7), and (−)-Gelsemolenine A(4) …”
mentioning
confidence: 99%
“…Much effort has been made to accomplish the total synthesis of gelsedine-type alkaloids. 4 The first total synthesis of ent-gelsedine was completed in 21 steps by Hiemstra and co-workers in 1999, which features the construction of a 7-azabicyclo[4.2.1]nonane system by intramolecular addition of an allene to an N-acyliminium intermediate followed by the construction of an oxindole moiety by the palladium-catalyzed Heck reaction. 5 Later, Fukuyama and co-workers accomplished a spectacular total synthesis of gelsemoxonine, 6a spirocyclopropane-isoxazolidine to furnish an azetidine moiety.…”
mentioning
confidence: 99%